2004
DOI: 10.2320/matertrans.45.1360
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Solution-Treatment on Microstructure and Mechanical Properties of Cast Fine-Grain CM 247 LC Superalloy

Abstract: This study investigates the effect of the solution-treatment, with solution temperatures from 1494 to 1533 K, on the microstructure and mechanical properties of fine-grain (65 mm) CM 247 LC superalloy. Tensile tests reveal that the yield strength of the alloy after multi-step 1527 K/2 h solution-treatment exceeds that after 1494 K/2 h solution-treatment. Additionally, the alloy after multi-step 1527 K/2 h solutiontreatment had a lower creep rate and greater rupture life than that after 1494 K/2 h solution-trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…The microstructure contains three distinct morphologies of γʹ precipitates: (i) irregularly shaped γʹ precipitates, 1-2 µm in size, predominantly located at the boundaries of the recrystallised grains and cell colonies; (ii) smaller cuboidal precipitates, 200-500 nm in size, uniformly distributed within the recrystallised grains; (iii) small precipitates of a similar size but more irregular morphology, uniformly distributed within the unrecrystallised grains. The morphology of the intragranular γʹ precipitates in the recrystallised grains was similar to that previously reported for conventionally cast CM247LC[28]. In addition, carbide particles were identified, ranging from 200 to 500 nm in size.…”
supporting
confidence: 83%
“…The microstructure contains three distinct morphologies of γʹ precipitates: (i) irregularly shaped γʹ precipitates, 1-2 µm in size, predominantly located at the boundaries of the recrystallised grains and cell colonies; (ii) smaller cuboidal precipitates, 200-500 nm in size, uniformly distributed within the recrystallised grains; (iii) small precipitates of a similar size but more irregular morphology, uniformly distributed within the unrecrystallised grains. The morphology of the intragranular γʹ precipitates in the recrystallised grains was similar to that previously reported for conventionally cast CM247LC[28]. In addition, carbide particles were identified, ranging from 200 to 500 nm in size.…”
supporting
confidence: 83%
“…The EDS results showed that SHT material contained large congregations of γ’-forming elements that are not present in the HSHT material. It is assumed that, by forming as segregates, these elements are not contributing to the precipitation of γ’ during the ageing treatment; therefore, the alloy deviates from the design volume-fraction, size and morphology of γ’ precipitates, all of which directly affect mechanical response [ 16 , 32 ]. The HSHT material does not visibly contain these segregates, suggesting that the heat treatment has fully solutionised these elements, allowing them to contribute to the forming of γ’ precipitates, increasing the γ’ volume fraction, resulting in an increased yield and UTS at the expense of a reduction in elongation or ductility [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…has presented that the solutionising at temperature of 1155 °C/3 h and 1185 °C/3 h without temperature droppings shown fine γ΄ precipitates homogeneously distributed throughout the matrix. A multi-step solution treatment [8]. from 1221 °C/2 h to 1260 °C/2 h, was applied to as-cast CM 247LC Ni-based superalloy.…”
Section: Introductionmentioning
confidence: 99%